Analysis of Wu's slip and CNTs (single and multi-wall carbon nanotubes) in Darcy-Forchheimer mixed convective nanofluid flow with magnetic dipole: Intelligent nano-coating simulation - Alzahrani, Faris; Ijaz Khan, M. (Materials science & engineering. B, Solid-state materials for advanced technology, 2022)
•Here ferromagnetic flow of viscous fluid is addressed.•Wu’s slip effects is considered.•Dipole moment interaction is accounted.•Both single and multi-walls carbon nanotubes are considered as a nanoparticles.•Water is considered as base fluid. The analysis of viscous materials flow subject to diverse configurations with remarkable physical applications has many utilizations in the electrical, mechanical, industrial, applied physics and mathematics fields. Besides these, carbon nanotubes (CNTs) have numerous applications in energy storage, nanotechnology, chemical sensors, industry, optics, structural diverse materials and conductive plastics. Such consideration in mind, ferro-fluid flow of viscous liquid submerged in CNTs towards a stretchable surface affected by magnetic dipole interaction is addressed. Mixed convection and Darcy-Forchheimer effects are accounted. The energy relation is discussed in the presence of radiative heat flux and viscous dissipation. First and second order velocity slips are implemented at the boundary surface. The governing expressions specifying the flow are altered into ordinary ones with the assistance of appropriate similarity quantities. The obtained ordinary system is computationally tackled via Runge-Kutta 4th Order Method (RK4OM). Our obtained outcomes reveal that velocity of working fluid particles declines with an enhancement in ferromagnetic interaction parameter and Darcy-Forchheimer number. Also, behavior of temperature distribution increases more speedily for heightening of radiative parameter and Biot number. Coefficient of skin friction (surface drag force) and Nusselt number (heat transport rate) are calculated in view of important flow parameter numerically. The range of parameters are β=0.0,0.3,0.5,ε=0.1,0.5,1.0,Fr=0.1,0.5,1.0,γ1=0.0,0.5,1.0,γ2=0.0,0.1,0.2,δ=1.0,5.0,10.0,R=0.0,0.2,0.5,Bi=0.5,1.0,1.5 and.λ=0.0,1.0,3.0.